2023
DOI: 10.3390/jpm13030405
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activity in the Effect of Transcranial Magnetic Stimulation Therapy for Patients with Depression: A Meta-Analysis

Abstract: Depression is a long-lasting mental disorder that affects more than 264 million people worldwide. Transcranial magnetic stimulation (TMS) can be a safe and effective choice for the treatment of depression. Functional neuroimaging provides unique insights into the neuropsychiatric effects of antidepressant TMS. In this meta-analysis, we aimed to assess the functional activity of brain regions caused by TMS for depression. A literature search was conducted from inception to 5 January 2022. Studies were then sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The reduced local activity in sensorimotor regions may be attributed to the consequence of exposure to treatments and depression-associated vulnerability. For treatment effects, a meta-analysis found that stimulation therapy for depression altered the activity in the right precentral gyrus, right posterior cingulate, left inferior frontal gyrus, and left middle frontal gyrus . After electroconvulsive therapy, fALFF was reported to decrease in the right precentral gyrus .…”
Section: Discussionmentioning
confidence: 99%
“…The reduced local activity in sensorimotor regions may be attributed to the consequence of exposure to treatments and depression-associated vulnerability. For treatment effects, a meta-analysis found that stimulation therapy for depression altered the activity in the right precentral gyrus, right posterior cingulate, left inferior frontal gyrus, and left middle frontal gyrus . After electroconvulsive therapy, fALFF was reported to decrease in the right precentral gyrus .…”
Section: Discussionmentioning
confidence: 99%
“…For treatment effects, a meta-analysis found that stimulation therapy for depression altered the activity in the right precentral gyrus, right posterior cingulate, left inferior frontal gyrus, and left middle frontal gyrus. 31 After electroconvulsive therapy, fALFF was reported to decrease in the right precentral gyrus. 32 Additionally, antidepressant resulted in decrease in hyperconnectivity within the limbic system.…”
Section: Discussionmentioning
confidence: 99%
“…A resting-state fMRI study has shown that the spontaneous brain activity of the precentral gyrus is reduced in MDD (Liang, Xue et al, 2020), while TMS treatment is associated with an increase in spontaneous brain activation in this region (Deng et al, 2023). A meta-analysis has also found that the gray matter volume of the precentral gyrus is reduced in depressed patients (Amidfar et al, 2021;Bora et al, 2012).…”
Section: Other Regionsmentioning
confidence: 99%